Iridofundal colobomas may lower severity of retinopathy of prematurity - Gangwe, Anil Babanrao; Chandra, Parijat; Takkar, Brijesh; Azad, Shorya Vardhan; Azad, Rajvardhan (Annals of Eye Science, 2018)
We report a case where unilateral iridofundal coloboma (IFC) was observed with asymmetric retinopathy of prematurity (ROP). Associated ocular abnormalities with IFC are present in nearly 15% of the cases; however its implications on course of ROP have not been reported thus far. IFC, damaging in its own respect, may be protective against disease progression in ROP.